RELATIONSHIP BETWEEN CONSUMER INVOLVEMENT AND BRAND PERCEIVED QUALITY ON FEMALE COSMETIC CONSUMERS AND PURCHASE INTENTION OF THE FOREIGN BRAND COSMETICS (STUDY IN FEMALE COSMETIC CONSUMERS IN JAKARTA) - Prakoso, Tribowo; Setiowati, Rini (Bina Nusantara University, 2012)
Cosmetic is a product of consumer goods that have a high level of competition. Brand on a product becomes an important identity that has always known to exist by the consumer. With the ease of foreign brands to be accepted in Indonesia is a substantial opportunity for the cosmetics company, specially foreign brands and are ready to compete with a variety of Indonesian a traditional cosmetic is earlier known and has value to consumers of Indonesian women. Eventually expected to provide useful information for companies in designing marketing promotions, even more so when the product is a cosmetic that is part and parcel of the woman.